Six new species of the genus Caccothryptus from the Himalayas (Coleoptera: Limnichidae) - Matsumoto, Keita (European Journal of Taxonomy, 2021)
Six new species of the genus Caccothryptus (Coleoptera: Limnichidae) are described from the Himalayan region: C. brendelli sp. nov., C. arakawae sp. nov., C. championi sp. nov., C. larryi sp. nov., C. tardarsauceae sp. nov. and C. abboti sp. nov. Photographs of type specimens with relevant morphological characters to distinguish species are provided.